Sistem Temu Kembali Informasi Dengan Metode Vector Space Model (Studi Kasus Biografi Pahlawan Indonesia) (Information Technology and Telematics, 2015)
ABSTRACT The design of information retrieval system (STKI) with Vector Space Model method (VSM) is to allow users to search for Indonesian hero biography quickly and accurately. VSM method gives a different similarity value for each document stored in the database, where the documents with the highest similarity value is placed at the very top of the search results. Biography Indonesian hero is a little history in the lives of the heroes of the independence of Indonesia. This thing we need to learn to appreciate the services of our national heroes who had fought for independence of Indonesia. Because there is a proverb, "a great nation is a nation that respects the services of pahlawanya". therefore constructing an information retrieval system biography Indonesian hero who can help facilitate the public to get to know and appreciate the heroes of the independence of Indonesia. Keywords: Information Retrieval System, Hero Biography